Metabolic Biomarkers for the Early Detection of Cancer Cachexia - O’Connell, Thomas M.; Golzarri-Arroyo, Lilian; Pin, Fabrizio; Barreto, Rafael; Dickinson, Stephanie L.; Couch, Marion E.; Bonetto, Andrea (Frontiers in Cell and Developmental Biology, 2021)
Cancer cachexia is a severe metabolic disorder characterized by progressive weight loss along with a dramatic loss in skeletal muscle and adipose tissue. Like cancer, cachexia progresses in stages starting with pre-cachexia to cachexia and finally to refractory cachexia. In the refractory stage, patients are no longer responsive to therapy and management of weight loss is no longer possible. It is therefore critical to detect cachexia as early as possible. In this study we applied a metabolomics approach to search for early biomarkers of cachexia.